Uncertainty and firm dividend policy – a natural experiment - Bonnie Buchanan; Xuying (Cathy) Cao; Eva Liljeblom; Susan Weihrich (Bank of Finland, 2016)
We examine how firms respond to uncertainty around U.S. tax policy changes, namely the individual level tax rate increases set to take effect on January 1, 2011 and January 1, 2013. We provide evidence that firms time the uncertainty in the tax environment and revise their dividend policy to an expected tax increase. We find that firms are likely to initiate their dividends or intensively increase their existing dividend amount one year before the expected tax increase. In addition, in 2012 when there is much less uncertainty on dividend tax changes than in 2010, firms are less likely to initiate a regular dividend but are more likely to initiate special dividends. The results suggest that firms facing less tax uncertainty are less likely to make long-term commitments on regular dividend payments but are more likely to take advantage of the last-minute low tax benefits by issuing special dividends. Furthermore, the response to the possible elimination of a tax cut was strongest in firms with high levels of tax-affected ownership, supporting the argument that when facing policy uncertainty, firms behave to prepare for the worst scenarios from the viewpoint of the shareholders, which in this case is a tax increase.
URN:NBN:fi:bof-201605021113
Keywords: G35; G32; G38; H32; 330